Development and Characterization of Self-nanoemulsifying Drug Delivery System Loaded with Fixed Oil of Semecarpus anacardium Linn. - Vyas, Manish (Asian Journal of Pharmaceutics (AJP), 2016)
Objective: Fruits and fixed oil of Semecarpus anacardium Linn. are used to treat various ailments in different Indian System of Medicine including Ayurveda. Despite having a wide array of therapeutic activities, it is also known for toxicity. Hence, there is a need to prepare a pharmaceutically acceptable dosage form to reduce its toxicity, enhance bio-availability, and explore the use of S. anacardium Linn. as a potent drug. In this study, an attempt has been made to prepare self-nanoemulsifying drug delivery systems (SNEDDS) for oral delivery of fixed oil. Materials and Methods: Various oils, surfactants and co-surfactants were investigated to prepare a stable SNEDDS of S. anacardium Linn. Emulsification time, droplet size and zeta potential, and dissolution studies were carried out to choose the best SNEDDS formulation. Stability studies of developed SNEDDS were carried out at 5°C, 25°C, and 40°C, respectively. Results and Discussions: Based on the emulsification time, droplet size and zeta potential after dispersion into aqueous phase, an optimized formulation (F19) consisting of fixed oil, Labrafil M1944CS, Tween 80, Transcutol P (10:60:30% w/w) were prepared. The dissolution profile of fixed oil of S. anacardium Linn. loaded SNEDDS in various medium showed that 100% of fixed oil released within 10 min irrespective of the pH of the dissolution medium. The prepared SNEDDS was found stable for 3 months. Conclusion: It can be concluded that the poorly soluble fixed oil of S. anacardium Linn. can be successfully loaded in SNEDDS formulation.